Soundtracks of Survival: A Phenomenological Exploration of Music Listening as Student Stress Coping - Wahyu Nugroho; Dinda Aimi Adzani; Ardelia Nabi Hermayana (Journal of Psychological Insight, 2026)
Students frequently experience psychological pressure due to the combination of academic demands and organizational responsibilities in university life. This study aims to explore how music listening functions as a coping strategy for managing academic and organizational stress in students’ lived experiences. The research employed a qualitative case study approach involving five undergraduate students who were actively engaged in both academic activities and campus organizations. Data were collected through in-depth interviews, observations, and documentation, then analyzed using data condensation, data display, and conclusion verification techniques. The findings reveal three main patterns: music listening reduces perceived academic and organizational stress, supports emotional regulation and sustained focus during demanding tasks, and helps maintain productivity in academic activities. The novelty of this study lies in its phenomenological exploration of music listening as an everyday coping practice embedded in students’ academic routines. These findings highlight the importance of recognizing simple self-regulation strategies that support students’ psychological well-being and academic sustainability.